Long-Term Follow-Up of Advanced Liver Disease after Sustained Virological Response to Treatment of Hepatitis C with Direct-Acting Antivirals: Outcomes from a Real-World Portuguese Cohort - Tiago Pereira Guedes; Pedro Fragoso; Carolina Lemos; Mónica Garrido; Joana Silva; Daniela Falcão; Luís Maia; Teresa Moreira; José Manuel Ferreira; Isabel Pedroto (GE: Portuguese Journal of Gastroenterology, 2019)
Background: Direct-acting antivirals (DAA) have revolutionized hepatitis C treatment, with high sustained virological response (SVR) rates reported, even in historically difficult-to-treat groups. SVR is associated with a decreased risk of hepatocellular carcinoma (HCC), need for transplantation, and overall and liver-related mortality. Data from real-life cohorts on the medium- to long-term outcomes of patients with advanced liver disease and DAA-induced SVR are still missing. Objectives: To report and analyze the long-term outcomes of DAA-induced SVR in a real-life cohort of patients with advanced liver disease. Method: In this retrospective, longitudinal, single-center study, we collected data from patients with chronic hepatitis C infection and advanced liver disease (cirrhosis or advanced fibrosis) that had initiated DAA treatment between February 2015 and January 2017. Results: A total of 237 patients were included. A treatment completion rate of 98.7% and an SVR rate of 97.8% (intention to treat: 96.6%) were found. Of the 229 patients with SVR, 67.2% were cirrhotic (64.2% Child-Pugh class A; 3.1% Child-Pugh class B) and 32.8% had stage F3 fibrosis, with an average follow-up of 28 months. The overall mortality rate was 19/1,000 person-years and the liver-related mortality rate was 9.5/1,000 person-years. The hepatic decompensation incidence rate was 25/1,000 person-years and the HCC incidence rate was 11.6/1,000 person-years. There was a sustained increase in serum platelet values during up to 2 years of follow-up. A history of pretreatment decompensation and baseline platelet and albumin values were significantly associated with the occurrence of adverse liver events after the end of treatment. Conclusions: A DAA-induced SVR remains durable and is associated with an excellent clinical prognosis in patients with compensated advanced liver disease and with improvement or disease stabilization in decompensated patients. SVR is associated with a low risk of – yet does not prevent – HCC occurrence or disease progression, especially in the presence of other causes of liver injury. It is recommended that these patients be kept under surveillance.